Towards an understanding of 'school' readiness: collective interpretations and priorities. Issue 5 (19th October 2020) - McLeod, Naomi; Anderson, Babs
ABSTRACT: This participatory action research study examined participants developing conceptual understanding of 'school readiness' to enhance the learning and well-being of young children as they progress through children's services. We worked collaboratively with early childhood educators, from a range of provision such as Private Voluntary Independent early childhood and care settings (PVIs), children's centres and schools in Knowsley Local Authority, who were interested in researching their own practice individually and collectively. We provide insight into the trusting, collaborative inquiry workshops that enabled participants to engage in a process of reflexivity, so they became more aware and critical of their own practice and were more open to a process of change. Collective priorities from different perspectives were identified for improving young children's transitions. The findings indicate a new appreciation for starting with the child's readiness for learning, alongside the need for more connections and continuity between providers and families of birth to 3 and 3-5 age ranges. Support for the home learning environment was found to be essential in supporting parents recognise their potential as the child's first educators. Participants applied their action research learning experience to inform a more open and respectful appreciation of other perspectives in daily collaborations with stakeholders.